2020
DOI: 10.1016/j.ijmecsci.2019.105185
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of rainbow elastic metamaterials

Abstract: In this study, we present an optimization scheme for the resonator distribution in rainbow metamaterials that are constitutive of a Π-shaped beam with parallel plate insertions and two sets of spatially varying cantilever-mass resonators. To improve the vibration attenuation of the rainbow metamaterials at frequencies of interest, two optimization strategies are proposed, aiming at minimizing the maximum and average receptance values respectively. Objective functions for both single and multiple frequency rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…The specific arrangement of (neighboring) resonators within engineered metamaterials is known to shape their acoustic functionality. Spatially graded resonator arrays can create bandgap widening (19), rainbow trapping (20)(21)(22), and acoustic mode conversion effects (23,24). The scales and tiling patterns on moth wings also show morphological gradation from the base to the apex of the wing, but the functional significance of this remains unknown.…”
Section: Mixed Scale Arrays As Acoustic Metamaterialsmentioning
confidence: 99%
“…The specific arrangement of (neighboring) resonators within engineered metamaterials is known to shape their acoustic functionality. Spatially graded resonator arrays can create bandgap widening (19), rainbow trapping (20)(21)(22), and acoustic mode conversion effects (23,24). The scales and tiling patterns on moth wings also show morphological gradation from the base to the apex of the wing, but the functional significance of this remains unknown.…”
Section: Mixed Scale Arrays As Acoustic Metamaterialsmentioning
confidence: 99%
“…1). The rainbow metamaterial can exhibit single or multifrequency bandgaps depending on whether the two sets of resonators attached to different side walls are symmetric [1,2].
Fig.
…”
Section: Datamentioning
confidence: 99%
“…The numerical simulation data could not only act as an alternative method of modelling the rainbow metamaterial, the modal shapes can reveal the underlying vibration attenuation mechanism that cannot be given out by the presented analytical model [1,2], which would aid readers to fully understand the rainbow metamaterials.…”
mentioning
confidence: 99%
“…Celli et al [ 34 ] found out the effect of bandgap widening by a spatial gradient and the disorder of resonators in rainbow metamaterial plates through experiments. Recently, Meng et al [ 35 , 36 ] proposed rainbow metamaterial beams with spatially varying cantilever mass oscillators, which possessed broadened one-dimensional bandgaps within multiple frequency ranges compared with periodic beams. These one-dimensional rainbow structures open new avenues for the design of PnCs and metamaterials with enhanced properties.…”
Section: Introductionmentioning
confidence: 99%